Tuber Yield and Quality of Potato (Solanum tuberosum L.) influenced by Flower Removal and Earthing Up at Eastern Tigray, Ethiopia - Hagos, Gebregwergis Fitsum (Journal of Agricultural Sciences (Belgrade), 2021)
Field experiment was conducted at Eastern Tigray, Ethiopia during summer season to determine the effects of flower removal and earthing up time on tuber yield and quality of potato (Solanum tuberosum L.). The experiment comprised of three flower removal stage and five earthing up time treatments, which were laid out in a randomized complete block design (RCBD) of 5x3 factorial arrangement with three replications. Data collected on tuber yield and quality parameters were analyzed using SAS version 9.2. The main and interaction effects of flower removal and earthing up time treatments were significantly affected marketable and unmarketable tuber number and yield, total tuber number and yield, large size tuber in weight and number. The medium and small size tuber in weight and number was also shown significantly affected by main effects but not by their interaction effects. Similarly, dry matter content had significantly (p < 0.05) affected by flower removal alone, but not by earthing up time and its interaction with flower removal. Generally, highest marketable tuber yield ( 30.25 ton ha-1), large size tuber in weight (424.9 g) and number (5) and total tuber yield (30.96 ton ha-1) was recorded from treatment of potato flower removed at bud stage earthed up at 15 days after complete emergence. Therefore, removal of potato flower at bud stage earthed up at 15 days after complete emergence and common cultivation can be practiced for better tuber yield and quality of potato.